People with Disabilities as Motivational Objects in the Kick Andy Talkshow Program: The Social Construction Approach of Reality Theory - Rizki Halim (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2021)
Most of the disability issues have not yet received proper representation in the media, even though quite a few people with disabilities in Indonesia. The depiction of persons with disabilities in the media often distorts them. Often people with disabilities with physical limitations are depicted incorrectly or even irrationally. The Social Construction of Reality (SCR) theory, introduced by Peter L. Berger and Thomas Luckmann, uses to analyze whether the Kick Andy television program supports the stigma of the disabled or can be a medium that changes the stigma that exists as constructs for the disabled-related community. Television viewers have a rationalistic cycle through three moments: externalization, objectivation, and internalization. This theory focuses on general meanings and constructions built by community groups to shape social order (rules, standards, values, and activities recognized in community groups). The study results show that guest stars with disabilities on the Kick Andy television program cannot separate from the social construction that has been formed in the community regarding their condition. The Kick Andy program also clarifies the social construction experienced by its guest stars, which uses as an object of motivation for the audience. The researcher found that the Kick Andy show, intentionally or unintentionally, still gave a lousy label to people with disabilities, even though the host then used the narration built as a background for inspiration.